Penguatan Potensi Minat Kefarmasian pada Generasi Muda Muhammadiyah sebagai Implementasi Konsep Hidup Sejak Dini - Primanitha Ria Utami; Devi Ristian Octavia; Fauza Nisfu Laili; Muhammad Rasyad Arrofiqi (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
Increased public awareness of the importance of health is a challenge for health workers, especially in the field of pharmacy, to show their existence in realizing the quality of public health by orienting services to improve the quality of life. The lack of teaching staff in pharmacy results in not optimal pharmaceutical competency training which has an impact of the lack of cincern on students' awareness of the pharmaceutical world so that students know the use and selection of rational drugs. The pesantren environment makes students pay less attention to their own health and the surrounding environment so that students are easily exposed to disease. The purpose of this service is to increase students' awareness of the pharmaceutical world so that they know how to use and select drugs rationally and increase the importance of their own health and the surrounding environment. The stages carried out are pretest, socialization of the importance of knowing the world of pharmacy, practice making preparations, games, evaluation, and quizzes. The results of this socialization provide results that al-mizan Muhammadiyah lamongan students have increased their understanding of the world of pharmacy, and know how to use drugs rationally.